Fisioterapeutas no atendimento à pessoa com deficiência física em reabilitação: representações sociais e perspectivas de futuro na inclusão social - Lima, Eduardo Marinho Cavalcante (2011)
The objective of this study is to verify and analyze the social representations of physical therapists, on the persons with physical disabilities and how this thinking contributes to their professional performance and, consequently, to an improvement in the quality of life and a social inclusion effective. It is important to know the vision of the physiotherapists, not only in the rehabilitation of functionality, but also, the conceptualization of physical disability and the expectations of future in the social sector for people with disabilities Participated In the survey 14 physical therapists who work in an institution of Teresina PI, that assists children, youths and adults, with physical disabilities, congenital or acquired, whose sequels affect the individual's motive conditions in the physical rehabilitation of the institution. The instruments used were the application of questionnaires with open and closed subjects and interviews semi-structured. The data tabulated and categorized were subjected to content analysis before the interviewees report. According the research, the physiotherapists represent the deficiency in the physiologic ambit, evidencing the motive alterations that the own deficiency presents that is, the pathological situation that the own disability presents a determinant for the limitations and incapacities. Already in the representation of deficiency in the social aspect, the professionals, approached that the atmosphere in that live it can influence in the life quality. However, when questioned about the legislations, existent and adopted, the professionals showed insecurity, not presenting enough theoretical embasamentos, needing more information and professional knowledge. To develop a humanized vision gone back to your patients' rights in the social inclusion and a perspective of promising future is of great importance for the improvement of the professional's social critical sense.